An assessment of ambient air quality in two major cities in the state of Kuwait - Alenezi, Raslan; Al-anezi, Bader (International Journal of Engineering and Technology, 2015)
In this study, hourly mean continuous air pollution data for the year 2010 from two monitoring stations in major urban districts in the State of Kuwait were analyzed. The ambient air quality in the Al-Mansouriah and Al-Jahra districts was evaluated in terms of the hourly average concentrations of selected major air pollutants during the winter and summer seasons. The diurnal variations of these pollutants were analyzed, and in-depth comparisons of the two pollutant concentrations for the two districts were conducted to determine the predominant sources of the air pollutants. The concentrations of CO, PM10 and NO2 in the two districts exhibited different patterns in the summer and winter due to differences in the activities that take place in the surrounding areas. The concentrations of SO2 were high in both cities because of the Al-Doha power plant and oil fields near the city in Al-Jahra. The ozone concentration is highly correlated with NOx emissions and is greater in the summer than in the winter. The results confirm that road traffic is a major source of air pollution in the Al-Mansouriah district. The Al-Doha power plant and the oil fields near Al-Jahra greatly affect the air quality in that district.